2013
DOI: 10.2147/ijn.s48197
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting inhalable chitosan-coated poly(lactic-co-glycolic acid) nanoparticles containing hydrophobically modified exendin-4 for treating type 2 diabetes

Abstract: Inhalable glycol chitosan-coated poly(lactic-co-glycolic acid) (PLGA) nanoparticles containing palmitic acid-modified exendin-4 (Pal-Ex4) (chitosan Pal-Ex4 PLGA NPs) were prepared and characterized. The surface morphology, particle size, and zeta potential of chitosan Pal-Ex4 PLGA NPs were investigated, and the adsorption and cytotoxicity of chitosan Pal-Ex4 PLGA NPs were evaluated in human lung epithelial cells (A549). Finally, the lung deposition characteristics and hypoglycemia caused by chitosan Pal-Ex4 PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…PLGA nanoparticles coated with glycol chitosan was shown to be more readily absorbed onto A549 cells than the non-coated PLGA nanoparticles. The chitosan-coated PLGA nanoparticles were found in the lungs up to 72 h after pulmonary administration, whereas non-coated PLGA nanoparticles were removed from the lungs 8 h after administration [132].…”
Section: Drug Deliverymentioning
confidence: 99%
“…PLGA nanoparticles coated with glycol chitosan was shown to be more readily absorbed onto A549 cells than the non-coated PLGA nanoparticles. The chitosan-coated PLGA nanoparticles were found in the lungs up to 72 h after pulmonary administration, whereas non-coated PLGA nanoparticles were removed from the lungs 8 h after administration [132].…”
Section: Drug Deliverymentioning
confidence: 99%
“…Smaller size relative to microspheres renders polymeric NPs a suitable drug carrier for parenteral administration. Moreover, it has been generally observed that NPs can translocate efficiently across epithelial surfaces relative to microparticles [5, 6]. Polymeric NPs also exhibit high stability in biological fluids compared to liposomes and solid lipid NPs.…”
Section: Introductionmentioning
confidence: 99%
“…ECM proteins induce migration and proliferation of cells (Badylak et al, 2001;Sarikaya et al, 2002). Nanoparticles formed from liposomes (Roursgaard et al, 2016), dendrimers (Kafil & Omidi, 2011), and PLGA (Lee et al, 2013) are toxic when given at similar concentrations to the same A549 cells. Proliferation of epithelial cells is important in COPD, as apoptosis of epithelial cells continues even after smoking cessation (Hodge, Hodge, Holmes, & Reynolds, 2005).…”
Section: Resultsmentioning
confidence: 99%